Ba(Zn1/3Ta2/3)O3 filled PTFE composites for microwave substrate applications. (1st January 2013) - James, Nijesh K.; Simna, P.S.; Ratheesh, R.
Ba(Zn1/3 Ta2/3 )O3 (BZT) ceramic filler material is prepared through solid state ceramic route. The phase purity and crystal structure of BZT filler have been studied using powder X-ray diffraction technique. Different weight percentage of BZT filler has been incorporated in the PTFE matrix through sigma mixing (SM), extrusion (E), calendering (C) followed by hot pressing (H) (SMECH) process. Distribution of the ceramic particulates in the PTFE matrix was analysed by scanning electron microscopy. The effect of BZT ceramic filler content on the microwave dielectric properties of the PTFE composites was studied in the microwave frequency region using X-band waveguide cavity perturbation technique. Moisture absorption characteristics of the composite samples are studied as per IPC-TM 650 2.6.2.1 method.